Unleashing methylammonium-guanidinium lead iodide hybrid perovskite spherulitic microstructures: a structural and morphological investigation - Mukul, Monika; Kaliaperumal, Selvaraj; Rani, Mamta; Tripathi, Surya Kant (MRS Communications, 2023)
Perovskites can offer an attractive replacement option for existing commercial solar technologies. Herein microstructure plays an important role in improving the efficiency and stability of solar cells. Previously unidentified spherulitic microstructures of self-assembled polycrystalline perovskites are explored in this report. For this an intermediate phase of a promising guanidinium (GUAI)-rich perovskite has been investigated for its structural and morphological properties. This study infuses new insight into the evolution of perovskite microstructure from heterogeneity to homogeneity, as a result unravels the structure of perovskite embryonic spherulites, lamellar arrangements, transcrystalline nature, novel spherulites bridging, hole nucleation, impingement, and defects.
Keywords: Microstructure; Morphology; Nucleation & growth; Perovskites; Phase transformation; X-ray diffraction (XRD)